Faktor-Faktor Penyebab Pertumbuhan Permukiman Kumuh Di Kelurahan Cambaya Kecamatan Ujung Tanah Kota Makassar - Viviani Petrus Masuang, Lidia; Latief, Rudi; Jufriadi, Jufriadi (Journal of Urban Planning Studies, 2024)
The purpose of this study was to find out what factors influence the growth of slum settlements in Sub Cambaya, District Ujung Tanah, Makassar City. This research was conducted using a quantitative approach, where data collection was carried out by distributing questionnaires to the sample who became respondents in this study. The results of this questionnaire will be processed using a chi-square analysis Based on the results of the analysis conducted, it is known that the factors that have a strong influence on the growth of slum settlements in Sub Cambaya, District Ujung Tanah, Makassar City are income factors, land ownership status, building conditions, and drinking water supply conditions.